Converging Religious Doctrine: Sunni-Shi’i Marriages in Indonesia - Faiz, Muhammad Fauzinudin; Nasution, Khoiruddin; Sodiqin, Ali (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2024)
Taking the floor in Bondowoso, this article sheds light on the cross marriage practices between Sunni-Shi’i communities. The main question addresses how the marriages converge religious norms and socio-cultural dynamics, considering the significant theological differences between the two. This study positions itself within the context of Islamic jurisprudence, highlighting the normative differences in marriage practices between Sunni-Shi’i traditions. Through in-depth interviews and participant observation, the findings reveal that love, economic considerations, and strong social support play crucial roles in overriding the different doctrines. Sunni-Shi’i couples in Bondowoso successfully take care of their relationships through mutual respect and open communication, contributing to broader social cohesion. The marriages between Sunni and Shi’i individuals in Bondowoso adhered to a combination of religious and state legal frameworks to ensure legitimacy and social acceptance. Some couples followed the Sunni Shafi’i school of thought ensuring that the marriage contract (akad nikah) included the presence of two witnesses and the guardian(wali) for the bride. In cases where Shi’i traditions were incorporated, the ceremony sometimes included additional blessings or teachings from Shi’i scholars, while the concept of temporary marriage (mut’ah) was explicitly avoided due to broader Sunni opposition. Additionally, all marriages were officially registered under Indonesia’s state law through the Office of Religious Affairs (KUA), aligning with national legal requirements for marriage recognition. [Berlatar di Bondowoso, artikel ini menyoroti praktik pernikahan antara anggota komunitas Sunni dan Syiah. Pertanyaan utama yang dibahas adalah bagaimana pernikahan tersebut mengharmoniskan norma-norma agama dan dinamika sosial budaya, mengingat adanya perbedaan teologis yang signifikan di antara keduanya. Studi ini berada dalam konteks yurisprudensi Islam, dengan menyoroti perbedaan normatif dalam praktik pernikahan antara tradisi Sunni dan Syiah. Melalui wawancara mendalam dan observasi partisipatif, temuan penelitian ini mengungkap bahwa cinta, pertimbangan ekonomi, dan dukungan sosial yang kuat memainkan peran penting dalam mengatasi perbedaan doktrin. Pasangan Sunni-Syiah di Bondowoso berhasil menjaga hubungan mereka melalui saling menghormati dan komunikasi yang terbuka, yang pada akhirnya berkontribusi terhadap kohesi sosial yang lebih luas. Pernikahan antara anggota Sunni dan Syiah di Bondowoso mengikuti kombinasi kerangka hukum agama dan negara untuk memastikan legitimasi serta penerimaan sosial. Beberapa pasangan sengaja mengikuti mazhab Syafi’i dengan memastikan bahwa akad nikah dilaksanakan dengan kehadiran dua saksi serta wali bagi mempelai wanita. Dalam kasus di mana tradisi Syiah turut dimasukkan, upacara pernikahan terkadang mencakup doa tambahan atau pengajaran dari ulama Syiah, sementara konsep pernikahan temporer (mut’ah) secara eksplisit dihindari karena adanya penolakan yang luas dari kalangan Sunni. Selain itu, semua pernikahan secara resmi didaftarkan sesuai dengan hukum negara melalui KUA, sejalan dengan persyaratan hukum nasional untuk pengakuan pernikahan.]